Seismic monitoring of CO2 geosequestration: CO2CRC Otway case study using full 4D FDTD approach - Glubokovskikh, Stanislav; Pevzner, R.; Dance, T.; Caspari, E.; Popik, D.; Shulakova, Valeriya; Gurevich, B. (Elsevier, 2016)
© 2016 Elsevier Ltd. Stage 2C of the Otway project by CO2CRC Limited was designed as a feasibility study of seismic monitoring to detect and characterise small-scale leakage of CO2-rich gas into a saline aquifer. Design of the monitoring program is based on a series of simulations conducted in 2007-2014. The gas plume is likely to be small in size and the contrast in elastic properties is also predicted to be relatively low. To maximise the chances of detecting the low-amplitude time-lapse signal we optimise the current time-lapse processing workflow using synthetic datasets for the entire baseline and monitor surveys. The datasets were obtained by an elastic 3D FDTD modelling approach for the actual field acquisition geometry and the most realistic model of the subsurface and distribution of elastic properties in the gas plume. To this end we built a full-earth static geological model of the Otway site with resolution typical for reservoirs in petroleum exploration. Distributions of the seismic properties were obtained from geostatistical interpolation between wells within the static model. The analysis of the synthetic datasets gives an estimate of the magnitude of the time-lapse signal and illustrates effects of the conventional processing procedures on the signal in the presence of the band limited random noise. We have found that the anticipated intensity of the time-lapse signal is comparable to the average intensity of the reflections observed within the target interval, and hence should be sufficient for the detection of the signal. We believe that the proposed modelling workflow is of methodological value since it provides a reliable basis for seismic feasibility studies and development of modelling-driven processing workflows.